2012
DOI: 10.5923/j.mm.20120205.12
|View full text |Cite
|
Sign up to set email alerts
|

Lean Problem: Why Conpanies Fail with Lean Implementation?

Abstract: Lean thinking approach was reported in many papers to be very efficient and straightforward way towards process improvements in terms of p roductivity and value adding act ivities ratio. On other hand, it was also discovered that the system which is working very well in Toyota might not give similar effective results in other companies. Many manufacturers have failed in achiev ing success of lean th inking imp lementation. Cu rrent study is seeking the reasons of failures in lean thin king imp lementation. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…For the implementation of QCCs, previous research has suggested that their successful implementations are based on few factors (Miina, 2012;Seyedhosseini et al, 2011), including the number of ideas have been submitted (Karlsson & Ahlstrom, 1996), implemented (Baides & Moyano-Fuentes, 2012;Winfield, 1994), and the time improvement participants spent in developing ideas (Marin-Garcia et al, 2008). This study followed Ma et al (2014) that the number of QCC meetings is a proxy to measure the quantity of QCCs, whilst the number of completed and presented QCCs is a proxy for quality of QCCs.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…For the implementation of QCCs, previous research has suggested that their successful implementations are based on few factors (Miina, 2012;Seyedhosseini et al, 2011), including the number of ideas have been submitted (Karlsson & Ahlstrom, 1996), implemented (Baides & Moyano-Fuentes, 2012;Winfield, 1994), and the time improvement participants spent in developing ideas (Marin-Garcia et al, 2008). This study followed Ma et al (2014) that the number of QCC meetings is a proxy to measure the quantity of QCCs, whilst the number of completed and presented QCCs is a proxy for quality of QCCs.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…This concept is based on the theory that every company has its own understanding of lean and should focus on its own production philosophy. A detailed description of the lean house is available in literature (Miina, 2012). Another approach is the implementation of lean accounting where the focus lies on cost reduction, while standard accounting focuses on cost maintenance (Schlichting, 2009).…”
Section: Leadershipmentioning
confidence: 99%
“…2.2.1 Improvement #7 Continuous improvement: The concept of continuous improvement is crucial to keep a lean conversion sustainable and is mentioned as being the most important step in a lean journey by Miina (2012). It takes place in cycles, where an organization never stops to question its processes.…”
Section: Culturementioning
confidence: 99%
See 2 more Smart Citations